THE ETIOLOGY OF NONCARIOUS CERVICAL LESIONS: A NEW CHALLENGE FOR THE 21ST CENTURY DENTIST - Marcelle de Sá Sppezapria; Maria Elisa da Silva Nunes Gomes Miranda; Telma Regina da Silva Aguiar (Portal de Periódicos da Marinha do Brasil, 2021)
The term noncarious cervical lesions (NCCL) refers to the loss of hard tooth tissue at the Cemento-Enamel Junction (CEJ), whose etiology is not related to bacterial involvement. The origin and progression of these cervical defects are considered multifactorial, being attributed to three main factors: abfraction, biocorrosion and abrasion. Such factors may be combined and associated with excessive force events applied during brushing, along with the abrasiveness of dentifrices, eating and/or parafunctional habits. These lesions may have different morphologies according to their main etiological factor, and may be wedge-shaped, oval or rounded. Our aim in this paper was to perform a literature review in order to present the challenges of the dental surgeon in identifying the different etiological factors of NCCL. Such challenge regards the study of the combination of these factors, as well as the achievement of an accurate diagnosis, requiring adequate knowledge of the etiology in order to prevent future lesions, stagnate existing ones, thus enabling the Dental Surgeon to treat NCCL effectively in the long term. However, there are still many controversies in the literature, making it necessary to develop more studies to elucidate the etiology of NCCL.